Analysis of human resources readiness strategies for small and medium enterprises in tourism development to face the new normal era of the Covid-19 pandemic - Nining Satriani; Hamidah Nayati Utami; Arik Prasetya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study aims to determine the strategy of developing human resources for small and medium enterprises in the field of tourism, as well as the quality of human resources for small and medium enterprises that affect the development of tourism during the pandemic and the government's response to the new normal era of the Covid-19 pandemic. This type of research is qualitative descriptive research. Research instruments include strategies for developing human resources for tourism MSMEs, quality of human resources, and strategies for improving the quality of human resources for tourism MSMEs. The data analysis used is the validity of the data, data reduction, and data presentation. The results of the analysis show that the Government first developed SME human resources through culinary training, bamboo weaving training, tourist attraction management training, and net wicker training. During the pandemic, the quality of SME human resources has a significant impact on the development of tourism in Loghia by increasing the credibility and innovation of SME products, improving the quality of tourism services, and improving the quality of local products. The government's strategy is to improve the quality of human resources for MSMEs for Tourism Development in Loghia through various ways, namely innovation, government adaptation, and collaboration with many related parties to support all policies and pay attention to and fight for the resolution of the downturn problem that occurs in tourism SMEs and employees. These findings hint at the need for improvement to create a good and sustainable business.